EFEKTIVITAS PELATIHAN TOKOH MASYARAKAT SEBAGAI PEER EDUCATOR SUAMI SIAGA DALAM PERAWATAN KEHAMILAN ISTRI DI WILAYAH KERJA PUSKESMAS I AJIBARANG - Renata, Desy Sosanti; Masfiah, Siti; Gamelia, Elviera (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2015)
The role of the husband is the most influential factor on a mother's pregnancy care in Ajibarang. By setting the husband as one of the focus in maternal health education programs can create behaviors that can improve the health of the mother. Peer education for husbands can be use to increase the knowledge and participation of alert husband. In order to increase the participation of husband, we need the necessary agents of change, who close with the husband, that is community leaders. Training community leaders as peer educators is expected to increase the alert husband's participation in wife's pregnancy care to reduce maternal mortality. The purpose of this study was to examine the effectiveness of training community leaders as peer educators of alert husband in pregnancy care in Ajibarang I Public Health Centre. The method used was a quasi experimental design with one group pretest and posttest design. Samples were community leaders obtained using purposive sampling as many as 31 . Analysis of the data used a pair t test and Wilcoxon test. The results of this study indicate that training community leaders effectively improve knowledge, attitudes, motivation, and skills of community leaders as peer educators of alert husband. It is expected that community leaders are able to make peer education of alert husband in their respective areas.